How does the practice of evisceration for open globe injuries at Groote Schuur Hospital conform to international standards - Zondi, Junaid (Division of Ophthalmology, 2018)
Background: Penetrating trauma can have devastating visual consequences and is often challenging to manage effectively, especially in the setting of severe trauma. The decision to perform a primary repair or a primary evisceration following an open globe injury can be a difficult one. Removal of an eye is not only traumatic but produces grief, anxiety and depression. It can result in a poor quality of life of the affected patients, and thus must be justified before it is performed. Before a primary evisceration can be considered, certain criteria need to be fulfilled. The affected eye must have acuity of no perception of light. A total afferent pupillary defect must be present. There must be prolapsed uvea and/or retina in the wound. Wounds should be longer than 20mm, or extend posterior to the equator of the globe. The fellow eye should be normal and the patient must be able to give informed consent. The primary evisceration rete at Groote Schuur Hospital appears to be higher than in other centers. If we do conform to the required criteria, then we are justified in performing primary eviscerations, but if we do not conform, then we need to improve our adherence in order to meet the required standards and improve our management. Purpose: a. To determine if the above criteria for primary evisceration are met in those undergoing primary eviscerations at Groote Schuur Hospital, and at which point(s) we strayed from the guidelines. b. To determine the rate of primary and secondary eviscerations following ocular trauma. c. To evaluate the visual outcomes, at 3 months, of patients who present with no perception of light vision and total afferent pupillary defect who meet some of the criteria for primary evisceration, but primary evisceration is not performed. Methods: A retrospective case series study was performed to identify all patients who were admitted to the ophthalmology ward at Groote Schuur Hospital following an open globe injury. The records of all patients who underwent primary evisceration were analyzed to evaluate whether or not the criteria were met and to determine the rates of primary and secondary evisceration at GSH. Results: There was a total of 249 open globe injuries admitted during the designated two year period. Of these, 212 (85.14%) were males and 37 (14.86%) were females. The number of patients undergoing primary evisceration was 61 (24.5%) and the number of patients undergoing primary repair was 175 (70.3%) and thirteen (5.2%) had other procedures. Of the 61 patients who underwent primary evisceration, 10 patients had missing data and were thus excluded. Therefore, out of 51 patients in whom the required data was available, a total of 37 (72.55%) patients met ALL the criteria required for a primary evisceration to be performed. A total of 11 (21.56%) patients did not meet the visual acuity criterion of no perception of light (10 were perception of light and 1 was hand movements vision). A total of 9 (17.6%) patients were documented to not have a total relative afferent pupillary defect. All patients had prolapsed uvea in the wound. Three patients (5.8%) had an "abnormally" seeing or poorly seeing fellow eye. Five (9.8%) were not documented as irreparable. The informed consent criterion was fulfilled in all patients. Secondary eviscerations accounted for 4.6% of surgeries done for open globe trauma. Of the patients that were eligible for primary evisceration, but instead had primary repair, the majority (77.7%) remained NPL and 88.8% had phthisis bulbi at 3 months. Conclusion: The majority of our evisceration cases met all the criteria for a primary evisceration. The two criteria which we did not fully adhere to were the visual acuity of no light perception and the presence of a total relative afferent pupillary defect. Visual acuity testing in the trauma setting is challenging, but we should improve on the accuracy of our testing of these two entities, and clearer documentation of all the criteria in our open globe injury cases especially if undergoing a primary evisceration. A few patients had an abnormally seeing fellow eye and still underwent PE due to the injured eye being irreparable. Our primary evisceration rate reflects our resource- limited setting and the severity of our ocular trauma cases. The poor visual acuity and poor outcome in the form of phthisis bulbi at three months in those who did not have a primary evisceration despite poor acuity appears to support our rationale for performing primary eviscerations in those with poor prognoses, given our resourcelimited setting.